Corporate governance and employee confidence in the Ghanaian banking sector: Mediating role of corporate reporting disclosures - Sharon Donnir; Kingsley Tornyeva; Timothy Ayamga; Francis Tagoe (Cogent Business & Management, 2023)
The study explored the relationship between corporate governance and the confidence of bank employees in the Ghanaian banking sector and further investigate the mediating role of corporate reporting disclosures. The data for the study was gathered through the administration of questionnaires to selected employees from the 23 banks operating in Ghana after the sector's crisis from the year 2018 to 2022. Using the stratified and purposive sampling technique, 276 bank employees constituted the study sample. The study employed the Partial Least Square Structural Equation Modeling (PLS-SEM) to analyze the data using the SMART-PLS software. The findings of the study revealed that, corporate governance significantly relates with employees' confidence; corporate reporting disclosures significantly relates with employees' confidence; corporate governance significantly relates to corporate reporting disclosures; and finally, corporate reporting disclosures mediate the relationship between corporate governance and bank employees' confidence. The study contributes new perspectives to literature; provides model for government, regulators and policy makers to review existing policies and initiate new policies on governance of banks; and a guide to managerial decisions and strategies. The study has critical implications for theory, policy and practice. Theoretically, the study explored the stakeholder theory and contributed to literature. From the perspective policy, the government, regulating agencies such as Bank of Ghana (BoG) and Securities and Exchange Commission (SEC) will be guided by the findings to review existing reforms and initiate new and sustainable policies. Finally, the empirical findings have significant practical implications for practitioners and management especially in the post crisis era.
Keywords: 650; corporate governance; corporate reporting; employee confidence; Ghanaian banking sector